Patterns and Meanings of English Words through Word Formation Processes of Acronyms, Clipping, Compound and Blending Found in Internet-Based Media - Rio Rini Diah Moehkardi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This research aims to explore the word-formation process in English new words found in the internet-based media through acronym, compound, clipping and blending and their meanings. This study applies Plag’s (2002) framework of acronym and compound; Jamet’s (2009) framework of clipping, and Algeo’s framework (1977) in Hosseinzadeh (2014) for blending. Despite the formula established in each respective framework, there could be occurrences of novelty and modification on how words are formed and how meaning developed in the newly formed words. The research shows that well accepted acronyms can become real words by taking lower case and affixation. Some acronyms initialized non-lexical words, used non initial letters, and used letters and numbers that pronounced the same with the words they represent. Compounding also includes numbers as the element member of the compound. The nominal nouns are likely to have metaphorical and idiomatic meanings. Some compounds evolve to new and more specific meaning. The study also finds that back-clipping is the most dominant clipping. In blending, the sub-category clipping of blending, the study finds out that when clipping takes place, the non-head element is back-clipped and the head is fore-clipped.